2009
DOI: 10.1073/pnas.0906397106
|View full text |Cite
|
Sign up to set email alerts
|

Three susceptible loci associated with primary open-angle glaucoma identified by genome-wide association study in a Japanese population

Abstract: Primary open-angle glaucoma (POAG) is the major type of glaucoma. To discover genetic markers associated with POAG, we examined a total of 1,575 Japanese subjects in a genome-wide association study (stage 1) and a subsequent study (stage 2). Both studies were carried out at a single institution. In the stage 1 association study, we compared SNPs between 418 POAG patients and 300 control subjects. First, low-quality data were eliminated by a stringent filter, and 331,838 autosomal SNPs were selected for analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 30 publications
7
109
1
1
Order By: Relevance
“…23 A couple of recent GWAS for POAG have identified sequence variants and genetic loci associated with POAG susceptibility in populations of European and East Asian ancestry. 28,29 The advantages of GWAS include the fact that a specific disease model is not needed, which can allow identification areas of previously unsuspected pathogenesis. It seems likely that pathogenesis of most cases of glaucoma, excluding those in which single gene defects have been identified, may be due to contributions from many different polymorphisms.…”
Section: Genetic Terms and Approachesmentioning
confidence: 99%
“…23 A couple of recent GWAS for POAG have identified sequence variants and genetic loci associated with POAG susceptibility in populations of European and East Asian ancestry. 28,29 The advantages of GWAS include the fact that a specific disease model is not needed, which can allow identification areas of previously unsuspected pathogenesis. It seems likely that pathogenesis of most cases of glaucoma, excluding those in which single gene defects have been identified, may be due to contributions from many different polymorphisms.…”
Section: Genetic Terms and Approachesmentioning
confidence: 99%
“…It is also quite important to properly assess the data from multiple sites in order to gain statistical power and identify latent variants associated with complex traits, especially when no major risk gene or locus was observed in the initial genome-wide association study (GWAS). Unlike the SNPs on the genes strongly associated with age-related macular degeneration (AMD) (3), we could not identify such SNPs in POAG that reached the genome-wide significant threshold (2). This is probably due to the fact that glaucoma seems to have more heterogeneous phenotypes than AMD and multiple gene-gene and geneenvironment interactions, each with a small effect, thereby possibly playing critical roles in the onset of the disease.…”
mentioning
(Expert classified)
“…This is probably due to the fact that glaucoma seems to have more heterogeneous phenotypes than AMD and multiple gene-gene and geneenvironment interactions, each with a small effect, thereby possibly playing critical roles in the onset of the disease. Therefore, we concluded that the discovered SNPs were ''modestly'' associated and would provide a foundation on which to build (2).…”
mentioning
confidence: 95%
“…This gene has now been shown to be significant in multiple independent GWAS in both normal tension glaucoma (NTG; see later) and POAG. Some have suggested its role is therefore on optic nerve susceptibility, 25 perhaps via effects on the TGF-beta pathway. 34 Certainly its role in glaucoma is now established, and further understanding of its role and effect on phenotype is now warranted.…”
Section: Glaucomamentioning
confidence: 99%